Analisis Risiko Keamanan Rantai Pasok di Perusahaan Jasa Ekspedisi Sebagai Dasar Penerapan ISO 28000 - Stefanny Meilinda; I Nyoman Sutapa (Jurnal Titra, 2019)
An expedition service company is a company engaged in shipping and transportation services. Companies need to handle security systems to meet the demands of customers needing to have international standards of security systems or certification.   ISO 28000 is a standard developed to answer the demands of the industry for the need to deal with security management standards. Security is an important thing for the company. This study aims to analyze the risk of supply chain security management systems in expedition service companies. The stages carried out in this design are the making of security policies, security targets and risk analysis designs using failure mode and effect analysis (FMEA). 13 FMEA risk analysis from all departments in the company, there are 6 who have high risk and in this study the response has been designed.